Fiduciary Security Execution after Constitutional Court Decision - R. Suharto1 , Siti Malikhatun Badriyah1 , Marjo1 , Muhammad Shafiyuddin Wafi1 , Muhammad Haidar Fakh (Institute of Medico-legal Publications Pvt Ltd, 2020)
Fiduciary collateral is one of the material guarantees, thus giving a fiduciary recipient a strong position. Thisis the main principle of fiduciary collateral, one of which is if the debtor defaults then the fiduciary collateralobject can be executed. With the decision of the Constitutional Court No. 18/PUU-XVII/2019, there arevarious conflicting opinions. This study aims to find evidence and analyze with legal studies relating tothe execution of fiduciary guarantees after the existence of the decision. The research method used is sociolegal. From the results of the study it can be seen that the existence of the Constitutional Court decisionlead to a variety of different interpretations. It is assumed that fiduciary recipients can no longer carry outexecutions based on their own power because they have to go through court. On the other hand, it is of theview that if the fiduciary recipient does not have the right to carry out executions based on the power ofthe fiduciary recipient himself and must go through a court of law then this is contrary to the principle ofmaterial security. The difference in interpretation can lead to legal uncertainty and lack of legal protectionfor fiduciary recipients who should have a strong position. Among other things in the case of debtor defaults,execution should be carried out without having to go through court.